Profile of traumatic brain injury (TBI) in relation with maxillofacial and thoracic injury Dr. Hasan Sadikin General Hospital, Bandung - Padmini Laxmi Pathmanathan; Gibran Tristan Alpharian; Agung Budi Sutiono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Traumatic brain injury (TBI) has a relation with concomitant injuries, which are mostlymaxillofacial and thoracic injury. This study aimed to know which injury was common inTBI patients and the difference in the severity of TBI when patients were associated withone or both types of injuries. This was a descriptive retrospective study. The data used wasmedical records from Department of Neurosurgery, Dr. Hasan Sadikin General Hospital,Bandung, Indonesia from the period of August 2015 to July 2016. Total sampling methodwas used in this study. The variables were patients with TBI, maxillofacial injury, thoracicinjury, accident related mechanism and non-accident related mechanism and the GlasgowComa Score (GCS). The total cases for this study were 47 patients. The highest case wasmales with 37 cases and 10 for females. Accident related trauma had 23 cases whereasnon accident related trauma had 24 cases. The total cases of maxillofacial injury were 32,thoracic were 6 cases whereby for both injuries were 9 cases. Patients with mild TBI were28 cases, moderate TBI were 13 cases, and severe TBI had 6 cases in total. The rate ofTBI was higher in single injury which was the maxillofacial injury. However, the thoracicand both injuries combined had higher severity of TBI compared to maxillofacial injury.